Adhesive small bowel obstruction in elderly patients: a single-center analysis of treatment strategies and clinical outcomes. (3rd July 2021) - Quero, Giuseppe; Covino, Marcello; Laterza, Vito; Fiorillo, Claudio; Rosa, Fausto; Menghi, Roberta; Fransvea, Pietro; Cozza, Valerio; Sganga, Gabriele; Franceschi, Francesco; Alfieri, Sergio
Abstract: Introduction: The incidence of adhesive bowel obstruction (ASBO) progressively increases with age. Strong evidences on the influencing role of age on ASBO clinical course and management are still lacking. Aim of this study is to retrospectively analyze the clinical outcomes of patients older than 65 years of age admitted to a tertiary referral Emergency Department with a diagnosis of ASBO. Materials and methods: We reviewed the clinical records of patients admitted for ASBO in the period 2014–2019. Patients were divided in elderly (≥65 years) and non-elderly (<65 years). Primary endpoint was to compare the all-cause in-hospital mortality and the occurrence of major complications in the two groups. Secondary endpoint was a comparison of clinical presentation, clinical course and management. Results: We enrolled 285 elderly and 492 non-elderly patients. Vomit was more frequent in the elderly (51.9% vs 34.6%; p < .001), while no difference was evidenced for the remaining symptoms of ASBO presentation. A higher rate of non-operative management (NOM) (26.3% vs 16.5%; p = .010), ICU admission (16% vs 0.6%; p < .001), mortality (2.1% vs 0.2%; p = .007) and cumulative major complications (8.8% vs 3.3%; p = .001), as well as a prolonged hospitalization (8.2 vs 5.4 days; p < .001) was evidenced in the ≥65 years group. Multivariate analysis identified increasing age (OR:2.8; 95%CI:1.09–7.2; p = .040) and Charlson comorbidity index ≥ 2 (OR:2.5; 95% CI:1.2–6.4; p = .050) as the only independent predictors of cumulative major complications. Conclusions: Despite the similarity in terms of clinical presentation, elderly patient present higher mortality rate and occurrence of major complications. A comprehensive geriatric assessment is recommended to optimize the diagnostic and clinical strategies in case of ASBO.